1989
DOI: 10.1162/jocn.1989.1.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Neural Processes Involved in Directing Attention

Abstract: Neural processes associated with two aspects of visual-spatial attention were investigated with event-related potential (ERPs): those that direct spatial attention to a given point in space and those that modulate the processing of sensory input after attention has been directed. The subjects were 6- to 9-year-old children (51 boys and 35 girls). An arrow cue directed attention from the central to peripheral visual field; targets were then flashed in the attended or ignored visual field 600 msec after the cue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
237
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(270 citation statements)
references
References 24 publications
30
237
2
1
Order By: Relevance
“…Thus, the ADAN appears to be sensitive to the anatomical identity of the cued hand (and not the attentional shift in external space) and has therefore been suggested to reflect attentional control processes based on somatotopically defined coordinates (see also Eimer et al, 2004). In contrast, the LDAP component does not appear to be sensitive to crossed hand postural changes, instead it has been found to be absent in blind people and in sighted people in complete darkness suggesting that this component is based on representations of visually mediated external space (Van Velzen et al, 2006; see also Harter et al, 1989). Furthermore, this suggests that the availability of visual spatial information influences mechanisms of endogenous spatial orienting.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Thus, the ADAN appears to be sensitive to the anatomical identity of the cued hand (and not the attentional shift in external space) and has therefore been suggested to reflect attentional control processes based on somatotopically defined coordinates (see also Eimer et al, 2004). In contrast, the LDAP component does not appear to be sensitive to crossed hand postural changes, instead it has been found to be absent in blind people and in sighted people in complete darkness suggesting that this component is based on representations of visually mediated external space (Van Velzen et al, 2006; see also Harter et al, 1989). Furthermore, this suggests that the availability of visual spatial information influences mechanisms of endogenous spatial orienting.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…1 These effects were similar to the results found in earlier studies which have measured ERPs elicited during covert shifts of visual attention. For example, Harter et al (1989) measured ERPs triggered by a central arrow cue indicating the side of an upcoming visual event. An early negative deflection at posterior electrodes contralateral to the direction of the induced attentional shift ('Early Directing Attention Negativity', EDAN) was followed by a contralateral positivity at posterior electrodes (LDAP; see also Yamaguchi et al, 1994;Hopf and Mangun, 2000;Nobre et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…First, we have shown that the posterior EDAN component reported in several earlier studies (cf. Harter et al, 1989;Hopf and Mangun, 2000) is not directly linked to the control of attentional shifts, but appears to reflect a lateralized visual response triggered by non-symmetrical visual cue stimulus (such as left-pointing and right-pointing arrows; see Van Velzen and Eimer, 2003, for more details). This component is absent in response to auditory attention cues , and when symmetrical visual cues are used , and the present experiment).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations